1978
DOI: 10.1002/ar.1091900207
|View full text |Cite
|
Sign up to set email alerts
|

Experimental studies on the acetylcholinesterase‐positive nerves in the ovary of the rat

Abstract: Adrenergic and acetylcholinesterase (AChE)-positive nerves were studied in the rat ovary four days after various experimental denervation procedures. Ablation of pelvic parasympathetic nerves (pelvic neurectomy [PN]) or abdominal vagotomy (AV) had no obvious affect on the adrenergic of AChE-positive nerves in the ovary. Section of the mesovarium resulted in the loss of all histochemically demonstrable adrenergic and AChE-positive nerves. Chemical sympathectomy with 6-hydroxydopamine (6-HD) resulted in the loss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0

Year Published

1980
1980
2006
2006

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(33 citation statements)
references
References 13 publications
1
32
0
Order By: Relevance
“…Although Burden & Lawrence (1978) found typical sympathetic nervous fibres reaching the ovary and showing acetylcholinesterase activity, acetylcholine was not found at ovarian level. However, the presence of acetylcholine receptors in the ovary, such as the M1 and M5 muscarinic receptors, has been demonstrated (Batra et al 1993, Arellano et al 1999, Mayerhofer et al 2003.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Although Burden & Lawrence (1978) found typical sympathetic nervous fibres reaching the ovary and showing acetylcholinesterase activity, acetylcholine was not found at ovarian level. However, the presence of acetylcholine receptors in the ovary, such as the M1 and M5 muscarinic receptors, has been demonstrated (Batra et al 1993, Arellano et al 1999, Mayerhofer et al 2003.…”
Section: Discussionmentioning
confidence: 78%
“…The ovarian nervous plexus and the vagus nerve have been involved only in the regulation of the blood flow (Burden & Lawrence 1978, Lawrence & Burden 1980). However, their importance in the ovarian functioning has not yet been determined.…”
Section: Discussionmentioning
confidence: 99%
“…Histological studies demonstrated that the ovarian sympathetic nerves innervate ovarian blood vessels as well as steroidogenic interstitial gland cells in the ovary [1,2]. Aguado and Ojeda [21] further demonstrated that severance of ovarian sympathetic nerves reduced the secretion of estrogen and progesterone at the proestrus stage in rats without changing ovarian blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…[The Japanese Journal of Physiology 55: [265][266][267][268][269][270][271][272][273][274][275][276][277]2005] The ovary is innervated by autonomic nerves in addition to being under the control of hormones (see review by Burden [1]). Histological studies in rats showed that the autonomic nerves innervating the ovary are sympathetic nerves and vagus nerves [2][3][4][5]. Recently, we demonstrated in anesthetized rats that stimulation of the sympathetic nerve that innervates the ovary causes a reduction in ovarian blood flow, while stimulation of the vagus efferent nerve that innervates the ovary had no effect on ovarian blood flow [6].…”
mentioning
confidence: 97%
“…However, there is also increasing evidence for the functional involvement of ovarian innervation by adrenergic and cholinergic nerves (see Burden, 1978;Burden & Lawrence, 1978, Tsafriri, 1988Luck, 1990). Stimulation by acetylcholine of bovine granulosa cells, which were undergoing luteinization in culture, has been reported to cause secretion of oxytocin and progesterone (Luck, 1990) and the muscarinic receptor antagonists scopolamine and atropine have been shown to inhibit the effect of acetylcholine (Luck, 1990).…”
Section: Introductionmentioning
confidence: 99%